IMPLEMENTASI HAK WARGA NEGARA MELALUI PENANGGULANGAN KEMISKINAN BERPERSPEKTIF GENDER PROGRAM KELUARGA HARAPAN TERHADAP MOTIVASI BELAJAR ANAK KELUARGA PENERIMA MANFAAT DI KABUPATEN SINTANG - Suparno Juri; Dessy Triana Relita (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2018)
The purpose research was to find out how the implementation citizens’ rights through poverty alleviation with a gender perspective is a family program hope towards the learning motiva- tion children beneficiary families in Sintang district. This research is motivated by the conditions poverty in Indonesia is quite high. Based on the research found that in Sintang: 1). The implementa- tion of Citizens’ Rights through Poverty Reduction with Gender Perspective The Family Hope Pro- gram has been implemented well; 2). Learning Motivation for Children Beneficiary Families is very good, it can be seen from the number KPM children who excel in both academic and non-academic fields. There are 59 children who excel both locally, nationally and internationally; 3). The Implemen- tation Citizens’ Rights through Poverty Alleviation with Gender Perspective Family Hope Program Against Learning Motivation Beneficiary family children are very relevant, because it has been able to facilitate underprivileged children to gain access to education as citizens’ rights, such as access to facilities in obtaining scholarships and relief tuition fees with assistance received in cash.